Cumulative Live-Birth Rates by Maternal Age after One or Multiple In Vitro Fertilization Cycles: An Institutional Experience - Dalia Khalife; Anwar Nassar; Ali Khalil; Johnny Awwad; Antoine Abu Musa; Antoine Hannoun; Lina El Taha; Fatin Khalifeh; May Abiad; Ghina Ghazeeri (International Journal of Fertility and Sterility, 2020)
Background The aim of this retrospective study is to investigate the cumulative live birth rate (CLBR) following one or more completed in vitro fertilization (IVF) cycles (up to 6 cycles) stratified by maternal age and type of infertility. Materials and Methods In this retrospective study, five hundred forty-seven women who received 736 fresh ovarian stimulation/embryo transfer cycles between January 2016 and December 2016 were included in the study at a tertiary care center located in Lebanon. Results In all women, the live birth rate for the first cycle was 33.0% [95% confidence interval (CI): 27.8-38.2]. The CLBR showed an increase with each successive fresh cycle to reach 56.9% (95% CI: 51.2-62.4) after 3 cycles and 67.9% (95% CI: of 62.5-73.0) after 6 cycles. The CLBR following 6 cycles reached 69.9% (95% CI: 63.8-75.6) in women younger than 35 years. In women older than 40 years, however, the live birth rate for the first cycle was signifi- cantly low at 3.1% (95% CI: 0.3-9.5) with a plateau in success rates after 4 cycles reaching 21.9% (95% CI: 9.2-40.0). Couples with different types of infertility had CLBRs ranging from 65% to 72%, with the exception of women with low ovarian reserve, where CLBRs reached 29.4% (95% CI: 10.3-56.0). Conclusion The CLBR at a referral center in a Middle Eastern country reached 67.9 % after 6 cycles, with variations by age and type of infertility treatment. These findings are encouraging for patients insisting to extend their treatment beyond 4 to 5 cycles.